Die vakfilosofie (Deel I): Die aard van die vakfilosofie* - Veldsman, T. H. (Koers, 1984)
The objective of this article series is to discuss the nature and task of Subject Philosophy. This particular article argues that Subject Philosophy forms part of all disciplines; deals with the key concepts of the discipline; attempts to answer "what is?" questions with respect to these key concepts; is related to the formal dimension of a discipline; and is limited to the presuppositions of the discipline .